2020
DOI: 10.1007/s11427-020-1661-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 24 asymptomatic infections with COVID-19 screened among close contacts in Nanjing, China

Abstract: Previous studies have showed clinical characteristics of patients with the 2019 novel coronavirus disease and the evidence of person-to-person transmission. Limited data are available for asymptomatic infections. This study aims to present the clinical characteristics of 24 cases with asymptomatic infection screened from close contacts and to show the transmission potential of asymptomatic COVID-19 virus carriers. Epidemiological investigations were conducted among all close contacts of COVID-19 patients (or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
636
4
28

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,153 publications
(726 citation statements)
references
References 13 publications
24
636
4
28
Order By: Relevance
“…There is strong evidence now, however, that many infected individuals who transmit COVID-19 are either minimally symptomatic or not symptomatic at all. In China, Chan et al (2020), Zou et al (2020), and Hu et al (2020) all reported the existence of asymptomatic individuals who tested positive for the SARS-CoV-2, and virus transmissions from asymptomatic carriers have been identified (Rothe et al 2020). Most recently, epidemiologists led by Shaman et al ) calculated that about 86% of infections in Wuhan, China, prior to the implementation of travel restrictions, were "undocumented" individuals, those with "mild, limited, or no symptoms" who accordingly were never tested.…”
Section: Editorialmentioning
confidence: 99%
“…There is strong evidence now, however, that many infected individuals who transmit COVID-19 are either minimally symptomatic or not symptomatic at all. In China, Chan et al (2020), Zou et al (2020), and Hu et al (2020) all reported the existence of asymptomatic individuals who tested positive for the SARS-CoV-2, and virus transmissions from asymptomatic carriers have been identified (Rothe et al 2020). Most recently, epidemiologists led by Shaman et al ) calculated that about 86% of infections in Wuhan, China, prior to the implementation of travel restrictions, were "undocumented" individuals, those with "mild, limited, or no symptoms" who accordingly were never tested.…”
Section: Editorialmentioning
confidence: 99%
“…The virus shedding has been noted not only in respiratory specimens but also in serum and stool. Importantly, viral shedding can occur for days for weeks furtively in asymptomatic carrier individuals especially children (3,9,10) and fecal shedding has been noted in patients without diarrhea. (10) Significant environmental contamination has been noted, including wash-basin, toilet bowl and air outlet fan surfaces in hospitalized patients.…”
mentioning
confidence: 99%
“…As Li reported, the median incubation period is 4-5.2 days and the 95th percentile of the distribution is 12.5 days [13]. Unfortunately, COVID-19 patients can be infective before the disease onset and maintain infective ability during the convalescent phase [3,4,14]. According to Cao's report [15], the shortest observed duration of viral shedding was 8 days, whereas the longest was 37 days.…”
Section: Discussionmentioning
confidence: 99%
“…In December 2019, a novel pneumonia resulting from SARS-CoV2, named coronavirus disease 2019 (COVID-19), emerged in Wuhan [1,2]. Due to the high viral contagiousness and transmission during the presymptomatic phase [3,4], COVID-19 progressively spread throughout China and has since become a global health issue [5]. In China, Wuhan city, the capital of Hubei province, became the center of a COVID-19 outbreak [6].…”
Section: Introductionmentioning
confidence: 99%